DHX36 binding induces RNA structurome remodeling and regulates RNA abundance via m6A reader YTHDF1 - Yuwei Zhang; Jieyu Zhao; Xiaona Chen; Yulong Qiao; Jinjin Kang; Xiaofan Guo; Feng Yang; Kaixin Lyu; Yiliang Ding; Yu Zhao; Hao Sun; Chun-Kit Kwok; et al. (Nature Communications)
Abstract RNA structure constitutes a new layer of gene regulatory mechanisms. RNA binding proteins can modulate RNA secondary structures, thus participating in post-transcriptional regulation. The DEAH-box helicase 36 (DHX36) is known to bind and unwind RNA G-quadruplex (rG4) structure but the transcriptome-wide RNA structure remodeling induced by DHX36 binding and the impact on RNA fate remain poorly understood. Here, we investigate the RNA structurome alteration induced by DHX36 depletion. Our findings reveal that DHX36 binding induces structural remodeling not only at the localized binding sites but also on the entire mRNA transcript most pronounced in 3’UTR regions. DHX36 binding increases structural accessibility at 3’UTRs which is correlated with decreased post-transcriptional mRNA abundance. Further analyses and experiments uncover that DHX36 binding sites are enriched for N6-methyladenosine (m6A) modification and YTHDF1 binding; and DHX36 induced structural changes may facilitate YTHDF1 binding to m6A sites leading to RNA degradation. Altogether, our findings uncover the structural remodeling effect of DHX36 binding and its impact on RNA abundance through regulating m6A dependent YTHDF1 binding.